Effect of short basalt fibers on energy-dissipating properties of lightweight rubberized concrete shear wall - Artem Zaitsev; Evgenii Matiushin; Victoria Shvetsova; Alexander Burukhin; Stepan Konev; Radmir Karamov; Skolkovo Institute of Science and Technology, Moscow – 121205, Russia. (Sustainable Structures)
To enhance the dynamic performance of shear walls, fine-grained rubberized basalt fiber concrete has been proposed as an alternative to conventional concrete. This is a promising material, yet the existing literature lacks an in-depth analysis of its energy dissipation properties. A comprehensive study was performed of fine-grained 100 x 100 mm cylindrical rubberized concrete specimens, both with and without basalt fibers, under low-cycle compression fatigue. The first concrete mixture had a volume fraction of 10 % crumb rubber, and the second concrete mixture contained a volume fraction of 0.3 % basalt fiber in addition to 10% crumb rubber. Scanning electron microscopy and computer tomography were used to validate the material's inner structure, adhesion, crumb rubber and basalt fiber distribution. To acquire the mechanical and dynamic properties of the material, hysteresis loops were obtained from 1000 cycles of compression fatigue tests under 0.1 and 0.05 strain rates on a servo-hydraulic machine through quasi-static laboratory tests. The obtained concrete properties were incorporated into VUMAT plasticity model of concrete and imported to ABAQUS for seismic analysis of reinforced concrete shear walls. A cyclic pushover analysis of the shear wall has been conducted to characterize its hysteretic behavior and energy dissipation for two consecutive concrete series, predicting long-term seismic performance. The concrete series with basalt fiber exhibited higher seismic resilience with hysteretic damping of 9.3% compared to 8.7% for the series without basalt fibers.